USING MULTIVARIATE COMMUNICATION APPROACH TO BUILDING THE UNIVERSITY MANAGEMENT SYSTEM - T. V. Simonyan; Y. S. Knyazeva (Advanced Engineering Research, 2014)
The structure of communication and its role in the management when building the University production and business integration are studied. The organization of the educational process on the basis of the communication component and its integration into the innovative educational activities of the University are considered. The key aim of building the communications process – to develop the approach to achieve the strategic objectives of the University – is presented. It is shown that various types of communication process (personalized and non-personalized, endogenous and exogenous) are used to provide individual attention to each student, to prove that the choice of the University is optimum. It is found that the communication processes of the University are always aimed to improve the quality and competitiveness of the educational services. It is noted that the industrial management theory and the complimentary sciences have created integration tools of the communication processes and have determined the opportunities for their codifiability. Some of these tools are of the methodological nature. Others are regarded as certain patterns, effects, principles, rules, and algorithms based on these models. Using the potential of this device determines the educational services quality.